2006
DOI: 10.1590/s0103-90162006000400005
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical analysis for soil moisture content under the no tillage cropping system

Abstract: Experiments in agriculture usually consider the topsoil properties to be uniform in space and, for this reason, often make inadequate use of the results. The objective of this study was to assess the variability for soil moisture content using geostatistical techniques. The experiment was carried out on a Rhodic Ferralsol (typic Haplorthox) in Campinas, SP, Brazil, in an area of 3.42 ha cultivated under the no tillage system, and the sampling was made in a grid of 102 points spaced 10 m × 20 m. Access tubes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 11 publications
2
16
0
8
Order By: Relevance
“…2). This result was consistent with several investigations which have noted that the coefficients of variation were low when the soil had higher water content (Robinson and Dean 1993;Grego et al 2006). Considering also the fact that soil moisture content in topsoil decreased gradually with permafrost degradation on the Qinghai-Tibetan Plateau, the CV of soil moisture content increased with permafrost degradation.…”
Section: Mean and Coefficient Of Variation (Cv) Of Soil Moisturesupporting
confidence: 92%
“…2). This result was consistent with several investigations which have noted that the coefficients of variation were low when the soil had higher water content (Robinson and Dean 1993;Grego et al 2006). Considering also the fact that soil moisture content in topsoil decreased gradually with permafrost degradation on the Qinghai-Tibetan Plateau, the CV of soil moisture content increased with permafrost degradation.…”
Section: Mean and Coefficient Of Variation (Cv) Of Soil Moisturesupporting
confidence: 92%
“…Thus, the soil moisture characterization in the sampling points is important in the compaction mapping because, by itself, it is already a factor that interferes with the measured RP values and, therefore, with their spatial variability. This finding was predicted by Grego et al (2006), who reported that agricultural experiments usually consider soil moisture as uniform in space and, consequently, because of that, the results are frequently misinterpreted. This fact renders inadequate the simple comparison through a correlation analysis of the different RP maps in the same area; thus, comparative control points become essential in studies on this topic.…”
Section: Resultsmentioning
confidence: 74%
“…Segundo Grego et al (2006), a maior variabilidade da estrutura de dependência espacial no período seco ocorre provavelmente devido ao processo de secagem do solo, e ocasionalmente podem aparecer algumas fissuras no solo, aumentando a aleatoriedade da variação espacial. Outro fato que deve ser destacado é que, quando a umidade do solo for baixa, outros fatores passam a influenciá-la, com maior participação na aleatoriedade da variação espacial.…”
Section: Resultsunclassified